Assessing strength of ferrite and martensite in five dual phase and two martensitic steels via high throughput nanoindentation to elucidate origins of strength - Eli Webber; Marko Knezevic (Journal of Materials Research and Technology)
This paper describes the main findings from an experimental investigation into overall and local strength of four dual-phase (DP) steels classified based on their tensile strength (TS) levels from DP590, to 780, to 980, to 1180, a martensitic steel (MS) 1700, and a high-strength low-alloy (HSLA) steel in rolled and additively manufactured (AM) conditions. The DP steels and the MS steel consist of ferrite and martensite, while the HSLA steel is solely martensitic. High throughput nanoindentation mapping is employed to measure the mechanical hardness of individual phases contributing to strength of the steels. A clustering methodology for correlating measured hardness and phase maps is conceived to infer hardness per phase. With increasing fractions of martensite, the hardness values of both ferrite and martensite are found to increase with more rapid increase in the hardness of ferrite than martensite. The phases increasingly dislocate with the fraction of martensite as rationalized by crystal plasticity modeling of strength of the steels. Initial slip resistances and a set of hardening parameters associated with the slip in ferrite and martensite are established to model the flow stress behavior of the steels. In modeling the co-dependent nature of crystallographic slip in ferrite and martensite, the initial dislocation densities are inferred and correlated with the measured hardness values. The hardness of martensite in the rolled HSLA steel is comparable to the hardness of martensite in the MS steel, while martensite in the AM HSLA steel is softer owing to the tempering occurring during the AM process.